White needle - Bowen, Carl (Bowen, Carl. Shadow Squadron., 2014)
A White Needle is code for dangerous chemical weapons that have been stolen. Syrian forces have come in possession of a White Needle, and it falls to the elite Shadow Squadron to find and stop them from launching it.